Lesion-induced insights in the plasticity of the insect auditory system - Lakes-Harlan, Reinhard (Frontiers in Physiology, 2013)
The auditory networks of Orthoptera offer a model system uniquely suited to the study of neuronal connectivity and lesion-dependent neural plasticity. Monaural animals, following the permanent removal of one ear in nymphs or adults, adjust their auditory pathways by collateral sprouting of afferents and deafferented interneurons which connect to neurons on the contralateral side. Transient lesion of the auditory nerve allows us to study regeneration as well as plasticity processes. After crushing the peripheral auditory nerve, the lesioned afferents regrow and re-establish new synaptic connections which are relevant for auditory behavior. During this process collateral sprouting occurs in the central nervous networks, too. Interestingly, after regeneration a changed neuronal network will be maintained. These paradigms are now been used to analyze molecular mechanism in neuronal plasticity on the level of single neurons and small networks.